Predictors of quality of life and depression among Korean‐American cancer patients and their family caregivers. Issue 12 (13th September 2018) - Yoon, Hyojin; Chatters, Linda; Kao, Tsui‐sui Annie; Saint‐Arnault, Denise; Northouse, Laurel
Abstract: Objective: This study examined social, cultural, and appraisal factors associated with Korean‐American cancer patients' and their family caregivers' quality of life (QOL) and depression. Methods: Data were from Korean‐American cancer patients and their family caregivers (N = 60 dyads) living in the United States. Study aims were examined using descriptive statistics and multiple regression. Results: For patients, higher social support and lower negative appraisal of illness predicted higher patient QOL; negative appraisal of illness also predicted higher patient depression. For caregivers, older age, having fewer traditional Korean values, and more modern (individualistic) values predicted higher caregiver QOL. Caregivers who held more modern values also had less depression. Conclusions: Higher support and less negative appraisal predicted better QOL in patients. For caregivers however, the type of cultural values they held (tradition or modern) was a key factor that predicted level of QOL and depression. Assessment of support and appraisal as well as attention to cultural values may enhance their QOL and reduce depression.